2007
DOI: 10.4049/jimmunol.179.12.8332
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Folding Defects in a RAG1 Variant Associated with Omenn Syndrome

Abstract: The RAG1 and RAG2 proteins are required to assemble mature Ag receptor genes in developing lymphocytes. Hypomorphic mutations in the gene encoding RAG1 are associated with Omenn syndrome, a primary immunodeficiency. We explored the biochemical defects resulting from a mutation identified in an Omenn syndrome patient which generates an amino acid substitution in the RAG1 RING finger/ubiquitin ligase domain (C325Y in murine RAG1) as well as an adjacent substitution (P326G). RAG1 C325Y demonstrated a 50-fold redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(76 citation statements)
references
References 53 publications
3
68
1
Order By: Relevance
“…The ring-finger domain's E3 activity prepares full-length RAG1 for the initiation of cleavage via the ubiquitylation of histone H3. Our results suggest that ubiquitylation of histone H3 spatially releases RAG1, however, we could not rule out the possibility that this transition into cleavage may also involve a conformational change in RAG1 [16]. The spatial release and an active conformation could be triggered simultaneously, and they are not necessarily mutually exclusive.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The ring-finger domain's E3 activity prepares full-length RAG1 for the initiation of cleavage via the ubiquitylation of histone H3. Our results suggest that ubiquitylation of histone H3 spatially releases RAG1, however, we could not rule out the possibility that this transition into cleavage may also involve a conformational change in RAG1 [16]. The spatial release and an active conformation could be triggered simultaneously, and they are not necessarily mutually exclusive.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies of the RAG1 ring-finger domain have revealed that the loss of E3 ubiquitin ligase activity correlates with decreased V(D)J recombination of episomal substrates [16,17]. Histone H3 was recently defined as a ubiquitylation substrate of the RAG1 ring-finger domain, suggesting a chromatin-mediated regulation of V(D)J recombination [18,19].…”
mentioning
confidence: 99%
“…A naturally occurring human mutation in this RING finger motif (C328Y) was found to cause the primary immunodeficiency disease Omenn's syndrome (20). A study of the equivalent mutation in mouse RAG1 (C325Y) showed that it greatly reduced recombination of an extrachromosomal plasmid, as did mutation of the neighboring residue (P326G) (21). Other RING finger residues critical for ubiquitin ligase activity appeared to contribute to robust recombination of extrachromosomal substrates (22).…”
Section: Significancementioning
confidence: 99%
“…cRAG1 is also partially defective in chromosomal recombination (Roman et al 1997), and the knock-in mouse displays a phenotype consistent with an overall reduced level of rearrangement and an increase in aberrant joints Talukder et al 2004). In an otherwise intact protein, mutations in the nc regions can lead to reductions in recombination far more severe than that seen with deletion of the entire nc regions (Roman et al 1997;Sadofsky et al 1994;Sadofsky et al 1993;Silver et al 1993;Simkus et al 2007). Furthermore, defects associated with mutations in ncRAG1 become more pronounced when the protein is present at limiting levels (Roman et al 1997;Simkus et al 2007), a situation likely to mimic normal recombination conditions (Leu and Schatz 1995).…”
Section: Rag1mentioning
confidence: 99%
“…<1% (Simkus et al 2007) P326G~W.T.~10%, <1% under limiting conditions (Silver et al 1993;Simkus et al 2007) C328S~W.T.~6% (Silver et al 1993) hC328Y OS (Villa et al 2001) hK136Q OS (Sobacchi et al 2006) hC192Y OS (Sobacchi et al 2006) hR314W B/T reduced immunodeficiency with granulomas (Schuetz et al 2008) All substitutions refer to the murine protein unless designated human (h). up~40-100% on extra-chromosomal substrates (Silver et al 1993;Sadofsky et al 1994) block in IgH V to DJ rearrangement in mouse (Liang et al 2002;Akamatsu et al 2003) RAG2∆388-413~100% (Silver et al 1993 T490A up supports recombination no G1/S-specific destruction of RAG2 accumulation of aberrant products in mouse thymocytes (Lee and Desiderio1999) persistence of SEC throughout cell cycle (Jiang et al 2004) hW416L OS (Sobacchi et al 2006) hK440L OS (Sobacchi et al 2006) hW453R OS (Noordzij et al 2002) hN474S SCID with maternal fetal engraftment (Villa et al 2001) hC478Y SCID (Villa et al 2001) hH481P SCID (Noordzij et al 2002) M502V OS (Sobacchi et al 2006) All substitutions refer to the murine protein unless designated human (h).…”
Section: Rag1mentioning
confidence: 99%